M4E West Connex Underwood and Parramata ventilation facility practicum report - Rojo, Ricci Ryan G. (Animo Repository, 2018)
The aim of the practicum project on the M4E Westconnnex Underwood and Parramatta Ventilation Facility is to provide construction phase services for the people on site during construction. The work consist of assisting the people on site by providing structural advice to adapt to the ever changing site conditions, by helping remedy the oversights done by the contractor, by answering queries and making clarifications on the initially produced detailed design drawings, and other similar problems being experienced during the construction phase. All of these things are being done at a fast pace where the queries should be answered back with a return of at most typically not more than three days, depending on the severity of the lapse or query, so as to not delay the construction being done. It is also the objective to apply learned technical knowledge and expertise to assist in the deliverables.